Analysis of the modification of tool surfaces by abrasive blasting and laser polishing - Wild, Thomas; Bestenlehrer, Marcel; Merklein, Marion (Defect and Diffusion Forum, 2020)
The surface treatment of tools plays an important role for the operational behaviour of forming processes. Up to now, industrial standard is the manual finishing of tool surfaces, which can lead to a varying quality of the surface finish and therefore influence the tool service life and the forming results. One method to perform the polishing operation automatically is to remelt the top layer of materials by laser polishing. This is accompanied by a considerable change in the material properties in this zone. Therefore, the effect of laser polishing with respect to the local modification of the tool surface is investigated in this study. The results of the investigations reveal that a precise adjustment of the laser parameters is required in order to reduce the roughness of the surface. The heat input also leads to a significant influence on the microstructure of the material. In this study laser polishing remelts the material up to a depth of approximately 20 µm. Furthermore, it can be observed that the heat input during the process results in a heat affected zone of up to a depth of 30 µm. As a contrast to laser polishing, abrasive blasting is investigated as a roughness increasing surface modification.
CRIS-Team Scopus Importer:2020-12-04
Keywords: Laser; Polishing; Surface Modification